A STUDY ON THE INCIDENCE OF OVARIAN DISEASES IN LOCAL COWS.‎ - Y.Artin, Immad; Ar.Fathalla, M.; Al-Azawi, H. (The Iraqi Journal of Veterinary Medicine, 1986)
The incidence of gross ovarian diseases were survid by studying 500 specimens obtained from Babylon slaughter house. The results of the study indicated that the incidence of the ovarian hypofunction (15.2%) was the highest, followed by cystic ovaries (2.8%), whereas the incidence of the ovarobursal adhesions was low (1.8%), while that of the parovarian cysts and cystic corpora lutea were lowest (1%). Additionally, the dimensions and content of the normal ovaries were included in the present study.